Организация многогрупповых компьютерных программ для расчета нейтронных полей и в реакторах атомных электростанций - Чернышов, Н. Н.; Панченко, А. Ю.; Сергеев, П. Ю.; Неежкаша, В. В.; Фурсова, Е. В. (ХНУРЭ, 2009)
In present work characteristic of computer programs for neutron-physical calculation of nuclear power plants’ reactors are shown. Especially shown, that the calculation of neutron fields is made using 3D-multi group programs, which take non-diffusion of neutron transportation info account. These programs can estimate inaccuracy of calculated functional. Also is considered issues of program organization and calculation models for active zones of reactors. It was made the conclusion that computer models for reactors calculation are created in order to allow following the history of integral technological unity. However, was discovered restrictions in working programs. Large physical dimensions of reactors contribute to irregularity of reactions running. To follow the irregularity it in is necessary to select appropriately the computer program.
Keywords: расчет нейтронных полей; атомный реактор